Cytokine levels in Type-2 Diabetes Mellitus (T2DM) Patients with Asymptomatic Bacteriuria (ASB) in Northern Andhra Pradesh - K.V.S.B. Vidya Sagar; P. Sarat Jyotsna; K. Sethumadhavan; Narasinga Rao Bandaru (Journal of Pure and Applied Microbiology, 2024)
Diabetes is a systemic inflammatory condition. The modulation of cytokine levels caused by Asymptomatic Bacteriuria (ASB) infection can lead to altered inflammatory status in various tissues and may affect their homeostasis and function. We aim to estimate the cytokine (IL-6, TNF-α and IL-10) levels in serum of diabetic individuals with and without ASB to study their clinical significance. The current study evaluates the role of cytokines in inflammation caused due to ASB in T2DM patients. Increase in IL-6 and TNF-α levels may indicate renal tissue damage caused due to inflammation by ASB. Whereas increased IL-10 levels is a possible indicator of persistent infection with bacteria which may lead to diabetic renal disease.